Conductive Hearing Loss Aggravates Memory Decline in Alzheimer Model Mice - Kim, Jin Su; Lee, Hae-June; Lee, Seonhwa; Lee, Ho Sun; Jeong, Ye Ji; Son, Yeonghoon; Kim, Jung Min; Lee, Yong Jin; Park, Min-Hyun (Frontiers in Neuroscience, 2020)
The study of cognitive impairment associated with hearing loss has recently garnered considerable interest. Epidemiological data have demonstrated that hearing loss is a risk factor for cognitive decline as a result of aging. However, no previous study has examined the effect of hearing loss in patients with cognitive problems such as Alzheimer’s disease. Therefore, we investigated the effect of conductive hearing loss in an Alzheimer’s mouse model. Positron emission tomography (PET) and magnetic resonance imaging (MRI) were used to evaluate changes in glucose metabolism and gray matter concentrations in the 5xFAD Alzheimer’s Disease (AD) transgenic mouse model with and without conductive hearing loss (HL). Conductive hearing loss was induced using chronic perforation of the tympanic membrane. Behavioral data from the Y-maze and passive avoidance tests revealed greater memory deficits in the AD with HL (AD-HL) group than in the AD group. Following induction of hearing loss, lower cerebral glucose metabolism in the frontal association cortex was observed in the AD-HL group than in the AD group. Although lower glucose metabolism in the hippocampus and cerebellum was found in the AD-HL group than in the AD group at 3 months, the gray matter concentrations in these regions were not significantly different between the groups. Furthermore, the gray matter concentrations in the simple lobule, cingulate/retrosplenial cortex, substantia nigra, retrosigmoid nucleus, medial geniculate nucleus, and anterior pretectal nucleus at 7 months were significantly lower in the AD-HL group than in the AD group. Taken together, these results indicate that even partial hearing loss can aggravate memory impairment in Alzheimer’s disease.